Land use affects total dissolved nitrogen and nitrate concentrations in tropical montane streams in Kenya - Jacobs, S.R.; Breuer, Lutz; Butterbach-Bahl, Klaus; Pelster, David E.; Rufino, Mariana C. (Elsevier, 2017)
African tropical montane forests are facing fast and dynamic changes in land use. However, the impacts of these changes on stream water quality are understudied. This paper aims at assessing the effect of land use and physical catchment characteristics on stream water concentrations of dissolved organic carbon (DOC), total dissolved nitrogen (TDN), nitrate (NO3-N) and dissolved organic nitrogen (DON) in the Mau Forest, the largest tropical montane forest in Kenya. We conducted five synoptic stream water sampling campaigns at the outlets of 13–16 catchments dominated by either natural forest, smallholder agriculture or commercial tea and tree plantations. Our data show a strong effect of land use on TDN and NO3-N, with highest concentrations in stream water of catchments dominated by tea plantations (1.80 ± 0.50 and 1.62 ± 0.60 mg N l−1, respectively), and lowest values in forested catchments (0.55 ± 0.15 and 0.30 ± 0.08 mg N l−1, respectively). NO3-N concentration increased with stream temperature and specific discharge, but decreased with increasing catchment area. DOC concentrations increased with catchment area and precipitation and decreased with specific discharge, drainage density and topographic wetness index. Precipitation and specific discharge were also strong predictors for DON concentrations, with an additional small positive effect of tree cover. In summary, land use affects TDN and NO3-N concentrations in stream water in the Mau Forest region in Kenya, while DOC and DON were more related to hydrologic regimes and catchment properties. The importance of land use for NO3-N and TDN concentrations emphasizes the risk of increased nitrogen export along hydrological pathways caused by intensified land use and conversion of land to agricultural uses, which might result in deterioration of drinking water quality and eutrophication in surface water in tropical Africa.